Faktor-Faktor Penentu Strategi Korporasi Dalam Perubahan Teknologi Dan Kemampuan Inovasi - Priyatiningsih, Katharina (Jurnal Keuangan dan Bisnis, 2022)
The management of a company needs to have a strategy to achieve effective and efficient performance and by understanding the appropriate corporate strategy it is also expected to be able to answer the dynamics of the environment, namely technological change with the company's ability to innovate. This research method uses a descriptive-explanatory approach to describe and explain technological changes and innovation capabilities that affect corporate strategy. The research instrument was used to collect data through a multilevel scale, interviews and observations from the analysis unit of property companies that are members of the real estate industry association. Data processing using PLS-SEM with a minimum sample of 10 times the maximum arrow pointing to the latent variable so that the minimum number of samples in this study was 20 samples, but to make it clearer, the data was enlarged to 32 samples. The findings of this study indicate that technological change in the property industry is more significant and influential than the ability to innovate. Changes in technology also have a significant impact on the ability to innovate. The order of determinants in technological change is financial technology, construction technology and new property technology, while the order of determinants in innovation capability is technological development, operations, and managerial.